Evaluation of salivary cortisol, RANKL and OPG levels in chronic periodontitis patients attending Hospital Universiti Sains Malaysia - Asif, Saba (2020)
Chronic periodontitis is a low grade inflammatory infection of supporting periodontal structure ocurring in the presence of pathogenic flora and plaque biofilm interaction with immune system over a period of time. Multiple risk factors such as smoking, alcohol intake, stress, obesity and metabolic syndrome, diabetes mellitus, other systemic diseases or conditions have been identified as a potential risk factors for this disease. The aim for this study is to assess and evaluate the association between levels of salivary cortisol, RANKL and OPG protein biomarkers in chronic periodontitis (CP) patients. In this cross sectional study, clinical periodontal parameters [periodontal pocket depth (PPD), clinical attachment level (CAL), plaque score (PS) and gingival bleeding index (GBI)] were performed and DASS-21 scores were assessed from the survey form. Protein concentrations for salivary cortisol, RANKL and OPG were assessed in study groups consisting of mild chronic periodontitis patients in group 2, moderate to severe chronic periodontitis patients in group 3 and healthy subjects in group 1 at Periodontic Clinics of School of Dental Sciences, Hospital Universiti Sains Malaysia. Mean levels for salivary cortisol, RANKL and OPG protein were higher for group 3 (moderate to severe chronic periodontitis) with 7.46 ng/ml, 0.23 ng/ml and 1.78 ng/ml. Higher depression, anxiety and stress score were also noted for group 3 (moderate to severe chronic periodontitis) from DASS-21 questionairre. DASS scores were significantly